1997
DOI: 10.1046/j.1365-2559.1997.d01-622.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of apoptosis in HIV‐myelopathy, myelodysplastic syndromes and non‐specific inflammatory lesions of the bone marrow

Abstract: Myelodysplastic syndromes, AIDS-related myelopathy and non-specific inflammatory reactions (mostly rheumatoid myelitis) are characterized by normo- to hypercellular bone marrow, but frequently display cytopenias in the peripheral blood. In the current study we have addressed the question whether this situation reflects an increased programmed cell death in haemopoiesis. For this purpose, the in situ end-labelling technique was applied to formalin-fixed and paraffin-embedded trephine biopsies derived from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…It is not, therefore, surprising the high prevalence found in this study. 6,14,19,20 The present study demonstrated a significant and independent association between the presence of ASB and both CD4 counts and viral load. These results imply that the more morbid the patients the higher the risk of asymptomatic bacteriuria and, possibly, the more vulnerability to bacterial and other opportunistic infections.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is not, therefore, surprising the high prevalence found in this study. 6,14,19,20 The present study demonstrated a significant and independent association between the presence of ASB and both CD4 counts and viral load. These results imply that the more morbid the patients the higher the risk of asymptomatic bacteriuria and, possibly, the more vulnerability to bacterial and other opportunistic infections.…”
Section: Discussionsupporting
confidence: 62%
“…However, the result is similar to those seen in patients with other immune suppressive clinical conditions like diabetes mellitus and sickle cell disease. 19,20 The risk factors for ASB in this patients were low CD4 counts and high viral load.…”
Section: Resultsmentioning
confidence: 82%
“…Several possibilities have been noted as the cause of such hematological abnormalities: the apoptosis of virusinfected cells, changes in the hematological environment, dysfunction of the thymus or the lymphoid system, change of cell division, or dysfunction of hematopoietic progenitor cells (1). Furthermore, a few reports have shown that the bone marrow of patients with AIDS displays morphological alterations similar to those of patients with myelodysplastic syndrome (2,31). The term "HIV myelopathy" has been used for this bone marrow pathology by some investigators (10,22).…”
mentioning
confidence: 99%
“…A high apoptotic rate, however, is by no means unique to MDS and has been reported in other conditions including aplastic anemia (15), Fanconi's anemia (16), beta thalassemia (17), human immunodeficiency virus (HIV) myelopathy, and other inflammatory myelitis (18).…”
Section: Discussionmentioning
confidence: 99%